Pengaruh Faktor Manajerial dan Faktor Lingkungan Eksternal terhadap Kinerja Perusahaan : Studi pada PT Bank Tabungan Negara (Persero) Tbk di Wilayah Bandung - Firdanti, Khairina Hafsa (Scimadly Publishing, 2025)
In the era of rapid globalization and digital transformation, Indonesia’s banking sector is expected to play a pivotal role in supporting national economic growth. To stay competitive and maximize their contribution to the economy, banks must continuously enhance their operational performance. Intense competition in terms of growth and market share emphasizes the importance of understanding the key factors that drive banking performance. This study investigates the impact of managerial capabilities and external environmental conditions on the performance of PT Bank Tabungan Negara (Persero) Tbk, a state-owned bank in Indonesia, during recent years. The results reveal that both internal managerial factors and external environmental factors significantly influence bank performance, with managerial capabilities playing a more dominant role. These insights highlight the critical importance of strengthening internal management skills while remaining adaptive to external changes. The study provides valuable guidance for banking management in developing effective strategies to improve performance through internal capacity building and environmental responsiveness.